Digital Literacy as a Challenge for Students to Attend Online Classes During COVID-19 Pandemic: A Critical Analysis - Prabhakar, Ashutosh; Ravindra Kumar (SCHOOL SCIENCE, 2021)
The recent revolution in digital technology has changed almost every aspect of our lives: how we communicate, work, enjoy our leisure time, and use the source of knowledge and information. At present, children are comfortable using different digital tools. However, it does not imply that they are digitally literate. The key here is that they still need to be supported and guided to be digitally literate. This will greatly propel their learning. All the more, digital literacy is significant for the first-time user especially due to challenges brought by the pandemic situation. Students’ pressing need to attend online classes forced them to be digitally literate, which was neglected earlier. Considering this existing gap, this study aimed to identify students’ digital literacy and the challenges faced in online learning. This survey-based study used the data from 100 students of Jawahar Navodaya Vidyalaya (JNV) Jethian, Gaya and D.A.V. Medical Unit, Gaya, India. The study revealed that the students need support and guidance to be digitally literate to enhance their learning experience. In this backdrop, the focus of different educational institutions needs to realign to address these challenges and prepare students equipped with digital competencies.